Prealgebra (7th Edition)

Published by Pearson
ISBN 10: 0321955048
ISBN 13: 978-0-32195-504-3

Chapter 4 - Section 4.6 - Complex Fractions and Review of Order of Operations - Exercise Set - Page 285: 43



Work Step by Step

$\frac{2+\frac{1}{6}}{1-\frac{4}{3}}$ $=(2+\frac{1}{6})\div(1-\frac{4}{3})$ $=(\frac{12}{6}+\frac{1}{6})\div(\frac{3}{3}-\frac{4}{3})$ $=\frac{13}{6}\div(-\frac{1}{3})$ $=-(\frac{13}{6}\div\frac{1}{3})$ $=-(\frac{13}{6}\times\frac{3}{1})$ $=-(\frac{13}{2}\times\frac{1}{1})$ $=-\frac{13}{2}$ $=-6\frac{1}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.